Using corpora in the language classroom - Reppen, Randi (Cambridge language education., 2010)
"Using Corpora in the Language Classroom shows teachers how to use corpora and corpus tools to expand student learning. Together with its companion website, this teacher-friendly book demystifies corpus linguistics with clear explanations, instructions and examples. It provides the essential knowledge, tools, and skills teachers need to enable students to discover how language is really used. Clear and concise, this volume provides: -An overview of corpus linguistics -Clear explanations of terminology -Tasks and activities that invite readers to interact with the material -Principled instructions for creating classroom materials and activities, including how to create corpora to address specific class needs"--Provided by publisher.